2013
DOI: 10.1007/s12160-013-9545-z
|View full text |Cite
|
Sign up to set email alerts
|

How Do Prompts for Attempts to Quit Smoking Relate to Method of Quitting and Quit Success?

Abstract: Quit attempts prompted by health professional advice appear to be more likely to involve gradual reduction and use of treatments. Those prompted by health concerns and cost appear more likely to succeed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 29 publications
3
13
0
Order By: Relevance
“…The findings confirm the results of previous studies evaluating different populations [26, 31-36], which underlined the underutilization of smoking cessation supports [37]. While some data suggest that attempts prompted by health professional advice were not more likely to succeed [38] or lead only to short-term success [39] , previous research showed that the use of assistance is associated with a greater success rate in comparison to no treatment [22, 40] . Accordingly, anti-tobacco campaigns and the increased availability of multiple forms of quit aids is assumed to facilitate the use of assistance and successful quitting [22].…”
Section: Discussionsupporting
confidence: 87%
“…The findings confirm the results of previous studies evaluating different populations [26, 31-36], which underlined the underutilization of smoking cessation supports [37]. While some data suggest that attempts prompted by health professional advice were not more likely to succeed [38] or lead only to short-term success [39] , previous research showed that the use of assistance is associated with a greater success rate in comparison to no treatment [22, 40] . Accordingly, anti-tobacco campaigns and the increased availability of multiple forms of quit aids is assumed to facilitate the use of assistance and successful quitting [22].…”
Section: Discussionsupporting
confidence: 87%
“…This is consistent with most reports that increasing cost is the tobacco control activity that most reliably increases quitting (Resnicow et al, 2014) but contrasts with retrospective surveys that most frequently report health reasons and/or physician advice are the main reasons for quitting (McCaul et al, 2006). The only prior study specifically examining environmental cues asked quitters to retrospectively report which cues contributed to their making a quit attempt (Ussher et al, 2013). Advice from a health care provider and a new or worsened tobacco related symptom were the two most common cues in that study (right hand column, Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…Smokers mostly acknowledge the harm they are doing to themselves and many report that they do not enjoy it – yet they continue to smoke (Fidler & West, 2011; Ussher, Brown, Rajamanoharan, & West, 2014). The reason is that nicotine from cigarettes generates strong urges to smoke that undermine and overwhelm concerns about the negative consequences of smoking, and the resolve not to smoke in those trying to stop (West & Shiffman, 2016).…”
Section: Introductionmentioning
confidence: 99%